NEUROPSYCHOLOGICAL DIAGNOSIS AND REHABILITATION In the context of Chilean terciary public attention - Ingrid Buller P. (CAEN, 2008)
The current article was developed from several conclusions obtained during a new and interesting professional practice experience of psychology, consisting of the introduction of neuropsychological diagnosis and rehabilitation services in the public tertiary health system context. During its accomplishment, it was possible to get to know thoroughly about the sufferings that brain stoke damaged patients have to face day by day, demonstrating their imperious need to obtain some type of therapeutic support parallel to the physiatric treatment among the predefined procedures in the current level of coverage of the AUGE - GES program. From this reflection it is expected to open new ideas and contributions that help to expand nervous system diseases rehabilitation treatments for patients attended in the public system, nowadays limited to movement or of daily activities therapies. This need of updating the treatments, derivative of the newest conceptions of an integral human being (biological, social and psychic), demonstrate the importance of including neuropsychological diagnosis and rehabilitation as service of public health and its consideration as critical issue for the current and future health authorities.